Cell-context response to germ layer differentiation signals is predetermined by the epigenome in regionalized epiblast populations - Niels Alvaro Menezes; Kathryn Johanna Peterson; Xiaogang Guo; Veronica Castiglioni; Adrija Kalvisa; Katarzyna Filimonow; Karen Schachter; Christina Maria Schuh; Athanasios Pasias; Luca Mariani; Joshua Mark Brickman; Jakub Sedzinski; et al. (Nature Communications)
Abstract Stem cells hold promise in regenerative medicine as they have the potential to differentiate into a variety of specialized cell types. However, mechanisms underlying stem cell potency and lineage acquisition remain elusive. Epigenetic modifications and genome accessibility prime cellular feedback to signalling cues, influencing lineage differentiation outcomes. Deciphering how this epigenetic code influences the context-dependent response of pluripotent cells to differentiation cues will elucidate how mammalian tissue diversity is established. Using in vitro and in vivo models, we show that lineage-specific epigenetic signatures precede transcriptional activation of germ layer differentiation programs. We provide evidence that while distinct chromatin accessibility and methylome states prime extraembryonic mesodermal fate decisions, it is DNA methylation, and not chromatin accessibility that predetermines the fates of neuroectoderm, definitive endoderm and neuromesodermal lineages. This study establishes that epigenetic machinery fine-tunes epiblast potency, allowing context-specific spatiotemporal responses to promiscuously used signalling cues controlling organogenesis.